2018
DOI: 10.1177/1753466618769514
|View full text |Cite
|
Sign up to set email alerts
|

Use of glucocorticoids in patients with COPD exacerbations in China: a retrospective observational study

Abstract: Background:Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are common in patients with underlying moderate to severe COPD and are associated with increased health and economic burden. International and Chinese guidelines recommend using glucocorticoids for the management of AECOPD because glucocorticoid therapy has been shown to benefit clinical outcomes. However, only scant data are available for current status of glucocorticoid therapy in hospitalized AECOPD patients in China. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 36 publications
(45 reference statements)
4
23
1
Order By: Relevance
“…As monotherapy treatment was the most commonly prescribed regimen in the primary study,24 we also analyzed the total medical expenditure for patients who received either nBUD or SCS alone in our analysis. Treatment with nBUD alone also resulted in significantly lower total medical expenditure of 8.7% compared with SCS alone ( P =0.0013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As monotherapy treatment was the most commonly prescribed regimen in the primary study,24 we also analyzed the total medical expenditure for patients who received either nBUD or SCS alone in our analysis. Treatment with nBUD alone also resulted in significantly lower total medical expenditure of 8.7% compared with SCS alone ( P =0.0013).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 5,067 patients with AECOPD admitted to hospitals between January and September 2014 were enrolled in the primary study and were eligible for this post-hoc analysis (Figure 1). Full details on the study design and methodology have been described previously;24 data underlying the findings described in this article may be obtained in accordance with AstraZeneca’s data sharing policy, described at https://astrazenecagrouptrials.pharmacm.com/ST/Submission/Disclosure.
Figure 1Study design. Any nBUD regimen is defined as nBUD monotherapy, sequential therapy (ie, initiated with nBUD at hospitalization and later switched to SCS), and sequential-combination therapy (initiated with nBUD at hospitalization and later combined with SCS).
…”
Section: Methodsmentioning
confidence: 99%
“…In fact, two studies suggested that the use of SCS, particularly at high doses and with long duration, in patients with AECOPD and respiratory failure, will not help the patients survive their AECOPD event. 25,26 A previous study in China showed that the most common daily dose of methylprednisolone injection was 40 mg, followed by 80 mg and 20 mg, while the most common daily dose of oral methylprednisolone was 20 mg, followed by 16 mg and 8 mg; in comparison, the most common daily dose of nebulized budesonide was 2 mg, followed by 4 mg and 6 mg. 15 In this previous study, the mean length of hospitalization was 12.2±6.2 days and the mortality rate during hospitalization was 1.2%. 15 In the present study, the dose of corticosteroids was of course lower in the NCS group compared with the two other groups, but the duration of treatment was similar.…”
Section: Discussionmentioning
confidence: 78%
“…The primary objective was to investigate the treatment patterns of AECOPD in hospitalized patients in China. 15 The outcomes of the original study were the percentage of patients receiving glucocorticoids by different routes of administration, doses and duration, mortality, and the mean length of hospitalization. 15 Forty sites (93.0%) were tertiary hospitals located in major cities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation